Considering health in US metropolitan long-range transportation plans: A review of guidance statements and performance measures. (July 2017) - Singleton, Patrick A.; Clifton, Kelly J.
Abstract: Transportation influences health primarily and most directly through traffic safety, air quality, physical activity, and accessibility. Despite the importance of all four components, only safety and air quality are typically considered during institutionalized transportation planning processes. This paper assesses how health impacts are considered in transportation planning by focusing on the long-range transportation plans that US metropolitan planning organizations develop. We analyzed the content of current plans from 25 large regions, reviewing how policy guidance statements and supporting performance measures addressed health. Goals and objectives exhibited an incomplete perspective of transportation's effects on health, focusing on safety, accessibility, and air quality, neglecting physical activity. Regional policies reflected national goals and planning requirements, which are rarely framed from a health perspective. Performance measures generally followed policy guidance, although measures of health and physical activity were lacking. Increased attention to the development of health-related performance measures and the data and analysis tools to support them is needed. By assessing the state of the practice and discussing potential approaches, this review informs a stronger and more comprehensive consideration of health within the institutionalized structure of US metropolitan transportation planning. Highlights: We reviewed how 25 long-range regional transportation plans consider health. Plan guidance statements and performance measures were analyzed for health. Goals focused on safety, air quality, and access, neglecting physical activity. Most plans lacked performance measures for health and physical activity. This review informs health considerations in metropolitan transportation planning.